(untitled) - Henslin, James M. (Boston, Massachusetts, 1997)
The book helps the readers discover all sorts of new and interesting information about themselves and the world around. This is the book that accompanies the textbook "Sociology : A Down-to earth approach" by James M. Henslin.
Keywords: Sociology